The birth of tragedy : out of the spirit of music - Nietzsche, Friedrich Wilhelm, 1844-1900 (Penguin classics., 2003)
In The Birth of Tragedy Nietzsche expounds on the origins of Greek tragedy and its relevance to the German culture of its time. He declares it to be the expression of a culture which has achieved a delicate but powerful balance between Dionysian insight into the chaos and suffering which underlies all existence and the discipline and clarity of rational Apollonian form. In order to promote a return to these values, Nietzsche critiques complacent rationalism of late nineteenth-century German culture and makes an impassioned plea for the regenerative potential of the music of Wagner. A wide ranging discussion of the nature of art, science, and religion, The Birth of Tragedy's argument raises important questions about the problematic nature of cultural origins which are still valid today.